Information and Communication Technologies (ICTs) For E-Learning in Tertiary Education in Sri Lanka: A Study of Undergraduates from State Universities in Colombo District - Galagedarage, Thushari Madhubhashini; Kaushallya Indrasena (International Journal of Media and Communication Research, 2023)
E- learning was introduced to tertiary education during the Covid 19 Pandemic. Therefore, the study aimed to investigate the opportunities and challenges faced by undergraduates in state universities in Colombo District in relation to e-learning. Technology Acceptance Model (TAM) was used as the main theoretical framework and the qualitative approach was applied through interviews and Focus Group Discussions (FGDs). Data were collected from all state universities in Colombo district using purposive sampling. The results showed that the majority of undergraduates have a positive attitude towards e- learning. Because e-learning is timesaving, convenient and cost-saving during the pandemic and socio-economic issues in the country such as fuel issues, power cuts etc. On the other hand, the undergraduates faced some challenges in e- learning such as a lack of ICT tools and equipment, connectivity issues, the cost of data, background noises, a lack of interaction with peers and teachers, health issues such as eye issues, anxiety etc. The results showed that the challenges of e-learning mainly occur due to the issues connected to ICTs. Therefore, the responsible authorities should take proper measures to provide adequate ICT infrastructure and resources for students to have a convenient and flexible e- learning system. In this context, it is also important that the state universities make the arrangements to have flexible learning for undergraduates. Therefore, hybrid learning allows undergraduates to attend traditional face to face sessions while also attending online classes, reducing transport issues, expenses, optimizing ICT infrastructure and resource utilization.